Developing Scalable Compliance Architectures for Cross-Industry Regulatory Alignment - Emmanuel Cadet; Lawal Abdulmutalib Babatunde; Joshua Oluwagbenga Ajayi; Eseoghene Daniel Erigh; Ehimah Obuse; Iboro Akpan Essien; Noah Ayanbode (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The rapid globalization of digital business ecosystems and the proliferation of complex, sector-specific regulations have amplified the challenge of achieving unified compliance across diverse industries. Organizations operating in multi-sector environments face fragmented regulatory obligations, often resulting in redundant processes, inefficiencies, and increased operational risk. This paper presents a comprehensive approach to developing scalable compliance architectures designed to enable cross-industry regulatory alignment while maintaining agility, cost-effectiveness, and resilience. The proposed architecture integrates modular, interoperable components capable of mapping and harmonizing overlapping regulatory requirements from finance, healthcare, manufacturing, energy, and other highly regulated sectors. By leveraging cloud-native infrastructure, artificial intelligence, machine learning, and regulatory technology (RegTech) solutions, the architecture supports automated rule interpretation, dynamic compliance control mapping, and continuous monitoring. Key features include a multi-layered governance model, a unified regulatory taxonomy, and an adaptive control library capable of aligning with evolving legal mandates and industry standards such as GDPR, HIPAA, PCI DSS, ISO 27001, and NERC CIP. A central innovation is the deployment of an intelligent compliance orchestration engine that enables real-time risk scoring, policy enforcement, and cross-sector reporting while reducing audit preparation times and minimizing compliance fatigue. The scalability of the framework is achieved through microservices architecture and API-driven interoperability, allowing seamless integration with existing enterprise resource planning (ERP), governance, risk, and compliance (GRC) platforms, and security information and event management (SIEM) systems. Using simulated enterprise deployment scenarios and multi-sector compliance datasets, the proposed architecture demonstrates significant improvements in regulatory coverage, operational efficiency, and cost optimization. Furthermore, the study explores governance models for maintaining ethical AI usage, data privacy, and cross-border compliance consistency. This work provides a blueprint for organizations seeking to unify fragmented compliance operations, enabling them to transition from reactive, sector-specific adherence toward proactive, enterprise-wide regulatory alignment that enhances trust, resilience, and competitive advantage in the global digital economy.
Keywords: Compliance Architecture; Regulatory Alignment; Governance; Risk, And Compliance (GRC); RegTech; Artificial Intelligence; Machine Learning; Continuous Compliance; Cross-Industry; Cloud-Native Infrastructure; Microservices; API-Driven Interoperability; Unified Regulatory Taxonomy; Operational Efficiency; Regulatory Technology; Multi-Sector Compliance